Pencegahan Perundungan (Bullying) Pada Anak di Lingkungan Sekolah - Thresia H.M.Y. Krey; Johan Rongalaha; Winna A.A. Senandi (LPPM Uncen, 2025)
Bullying is unpleasant behavior whether verbal, physical or social, whether it occurs in cyberspace or in everyday social environments. Bullying can occur at work, at school or on campus and among friends. The consequences of this bullying are that the victim will feel insecure and uncomfortable, feel hurt and depressed. Usually bullying is carried out by individuals or in groups. Perpetrators carry out bullying to hurt other people physically or emotionally, and find a sense of satisfaction when they have bullied their victims Meanwhile, victims of bullying are generally those who look weak and different from their environment, for example physical differences such as skin color, hair shape, body size, and also non-physical differences such as the way a person dresses, the way they speak. Bullying can happen to anyone, and without us realizing it, even school environments that are considered safe are places where bullying occurs most often. Legal education on